2000
DOI: 10.1152/ajpheart.2000.278.3.h688
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear changes of transmembrane potential caused by defibrillation shocks in strands of cultured myocytes

Abstract: Organization of cardiac tissue into cell strands and layers has been implicated in changes of transmembrane potential (DeltaV(m)) during defibrillation. To determine the shock-induced DeltaV(m) in such structures, cell strands of variable width [strand width (SW) = 0.15-2 mm] were grown in culture. Uniform-field shocks with variable strength [shock strength (SS) = 2-50 V/cm] were applied across strands during the action potential (AP) plateau, and DeltaV(m) were measured optically. Three different types of Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
97
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 36 publications
10
97
0
Order By: Relevance
“…36,37 The magnitude of the secondary sources created by an obstacle that interrupts the intracellular space depends upon the size of the obstacle and its distance from other obstacles. 38,39 The smaller is the obstacle, the smaller are the magnitudes of the secondary sources adjacent to it. Thus, the large, broad connective tissue septae throughout the myocardium would be expected to create much larger secondary sources than the much smaller obstacles created by the plunge needles.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 The magnitude of the secondary sources created by an obstacle that interrupts the intracellular space depends upon the size of the obstacle and its distance from other obstacles. 38,39 The smaller is the obstacle, the smaller are the magnitudes of the secondary sources adjacent to it. Thus, the large, broad connective tissue septae throughout the myocardium would be expected to create much larger secondary sources than the much smaller obstacles created by the plunge needles.…”
Section: Discussionmentioning
confidence: 99%
“…6 The reason for the dominance of virtual anodes is the negative asymmetry in the membrane response during the AP plateau, when negative polarizations are much larger than positive polarizations. 7,8 It should be added that even cathodal SS-⌬V m exhibited negative polarizations at some locations, indicating that there were intramural virtual anodes immediately under the epicardial surface (within Ͻ250 m).…”
Section: Intramural Virtual Electrodesmentioning
confidence: 99%
“…The ⌬V m of this type were previously described in cell cultures. 7,16,17 Recently, it was found that the occurrence of such ⌬V m was paralleled by cell uptake of the membrane-impermeable dye propidium iodide in the areas of negative but not positive ⌬V m , 18 indicating that such biphasic ⌬V m are the result of electroporation at sites of negative polarization. Membrane electroporation was implicated in the detrimental effects of shocks, such as loss of excitability and mechanical function, 19 generation of postshock arrhythmias, and failure of defibrillation at very strong shocks.…”
Section: ⌬V M Waveformsmentioning
confidence: 99%
“…It was found that the asymmetry of V m response was reduced by the application of nifedipine, a blocker of the L-type calcium current, 6 because of an increase in positive ⌬V m and that the asymmetry was insensitive to inhibitors of outward potassium currents. 5,6 This indicated that the ⌬V m asymmetry is attributable to the outward flow of Ca current in depolarized tissue, where V m rises above the I Ca reversal potential.Regarding the mechanism of nonmonotonic ⌬V m , the positive V m shift at sites of large negative ⌬V m suggests an increase in the net inward current at these locations. There are two main hypotheses explaining the mechanism of such ⌬V m .…”
mentioning
confidence: 97%
“…[1][2][3][4][5][6][7] Stronger shocks induce ⌬V m of the second type, which is characterized by a nonmonotonic behavior of negative ⌬V m when strong hyperpolarization is followed by a positive V m shift. 4,5 In addition, the amplitudes of both positive and negative ⌬V m do not increase proportionally with increasing shock strength but reach saturation levels and then decrease. 1,5 Several studies investigated cellular and ionic mechanisms of nonlinear ⌬V m .…”
mentioning
confidence: 99%